The Application of Integrated Management Information Systems of Community Service Program in Universitas Muhammadiyah Yogyakarta - Yulia Ariska Sudarsono; Nur Hayati; Rahmat Adiprasetya; Agem Jaya Dini (Journal of Electrical Technology UMY, 2017)
Community service program is a compulsory subject for all students in Universitas Muhammadiyah Yogyakarta (UMY). The existing information system of community service program in UMY is still run conventionally starting from registration system, group division and work area announcement. Meanwhile, students should come and ask directly to Office of Research, Publication, and Community Service to get all the information related to the program. This current system is complicated not only for students but also for officer who manage all data about community service program in UMY. Manually administered management cause frequent errors in invading data and takes a long time to complete the activity. Researchers initiated solution to overcome this problem by implement an application of management information system. This research has developed a web-based application that can be used to manage registration, personal data filling, and periodic scheduling for students whom take the community service program. Various parameters implementation as success determinant of system creation has been applied, so obtained a decent system used. The application is based on windows operating system that easily could be accessed through web interface. System testing has been done both from users (students) side and admin. the form of the webbased application developed has followed the standard manual form so that the system can work effectively and efficiently.